2022
DOI: 10.3390/ijms23063180
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring ZE21B Alloy with Nature-Inspired Extracellular Matrix Secreted by Micro-Patterned Smooth Muscle Cells and Endothelial Cells to Promote Surface Biocompatibility

Abstract: Delayed surface endothelialization is a bottleneck that restricts the further application of cardiovascular stents. It has been reported that the nature-inspired extracellular matrix (ECM) secreted by the hyaluronic acid (HA) micro-patterned smooth muscle cells (SMC) and endothelial cells (EC) can significantly promote surface endothelialization. However, this ECM coating obtained by decellularized method (dECM) is difficult to obtain directly on the surface of degradable magnesium (Mg) alloy. In this study, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…After coating modification, the NiTi alloy showed better cell proliferation than BN samples, with 1.5 times higher cell number on day 5, which might stem from the involvement of exosomes in information exchange between HUVECs, thereby promoting the proliferation of HUVECs, which was consistent with previous findings that exosomes promoted cell proliferation. [55,56] Several studies showed [5,16,57] that the speed of endothelial cell proliferation and migration was critical for stent endothelialization. A scratch assay was employed to assess endothelial cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…After coating modification, the NiTi alloy showed better cell proliferation than BN samples, with 1.5 times higher cell number on day 5, which might stem from the involvement of exosomes in information exchange between HUVECs, thereby promoting the proliferation of HUVECs, which was consistent with previous findings that exosomes promoted cell proliferation. [55,56] Several studies showed [5,16,57] that the speed of endothelial cell proliferation and migration was critical for stent endothelialization. A scratch assay was employed to assess endothelial cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfonation is an effective chemical modification method of HA molecules, which can not only improve their stability in vivo but also greatly improve a variety of biological functions, such as antiinflammatory, promoting physiological cell proliferation, and so on (Yu et al, 2020). Data showed that HA with a higher sulfonation degree had stronger functions of inhibiting inflammatory macrophages, promoting the adhesion, proliferation, and migration of EC and regulating and maintaining the contractile phenotype of SMCs (Yu et al, 2020), which is a promising potential FIGURE 6 | Fabrication of the biomimetic vascular basement membrane with the ECM secreted from the SMC and EC controlled by HA micro-patterned on the non-biodegradable and biodegradable material surfaces (Liu et al, 2022).…”
Section: Hyaluronic Acid Hydrogelsmentioning
confidence: 99%
“…Inspired by another de-cellularized technology, the ECM secreted by the HA-patterned EC was deposited on the cardiovascular implanted material surface ( Figure 6 ), which enhanced their biocompatibility ( Zou et al, 2019 ). The structure and function of the vascular basement membrane provide more enlightenment, and the ECM secreted by the HA-patterned EC and SMCs endows the materials with stronger multi-functions than the single HA-patterned EC-ECM ( Liu et al, 2022 ).…”
Section: Biomaterials Prepared With Hyaluronic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the application of this doublelayer ECM is limited because it is not easy to be directly prepared onto the biodegradable or uneven materials. To solve this problem, Liu et al dispersed the double layer ECM into normal saline using the ultrasonic vibration method, and then self-assembled it onto the surface of biodegradable Mg alloy (ZE21B) (Figure 4), thereby improving the corrosion resistance and biocompatibility of ZE21B [97]. It is unknown whether the process of preparing the ECM solution by ultrasonic vibration will cause losses to its components.…”
Section: Nature-inspired Ecm Coatingmentioning
confidence: 99%